Lymphoma of the lip after kidney transplantation: a case report - Payet Xavier; Raybaud Hélène; Kipper Morgane; Fino Enzo; Voha Christine (EDP Sciences, 2020)
Introduction: In transplant recipients, the risk to develop cancer increases 4 fold compared to general population due to the immunosuppressive treatment. Observation: A 68 years old woman, kidney transplanted four years ago, presented with a slowly growing swelling over her left lip since six weeks. The histopathological analyses showed a non Hodgkin lymphoma. Comment: Post-transplant lymphoproliferative disorders (PTLD) is a complication developing after solid organ transplantation or allogenic hematopoietic stem cell transplantation. Immunosuppression due to the immunosuppressives drugs is considered as the most important risk factor and the incidence rate depends of transplant type, age and risk of primary Epstein-Barr virus infection. Conclusion: PTLD is a rare but serious complication. It must be suspected in all cases of intra-oral mass for a transplanted patient and requires a histopathological analysis for early diagnosis and appropriate treatment.